Nanoscale restructuring of the immune synapse with an engager enhances NK cell function - Khodor S. Hazime; Sam Sheppard; Olatz Niembro-Vivanco; Cathal Hosty; Heather Thomas; Christopher Loosbroock; Leanne Peiser; Daniel M. Davis (Proceedings of the National Academy of Sciences, 2025)
Engagers are antibody-based therapies which bind immune cell receptors and a target cell ligand. Next-gen engagers typically bind two activating receptors, but the effect of this on immune synapse formation and signaling is unknown. Here, we coligated activating receptors CD16a and NKG2D on natural killer (NK) cells with a CD33-binding anti-acute myeloid leukemia (AML) engager. Superresolution microscopy revealed that coligating CD16a and NKG2D with a single molecule triggered their nanoscale coclustering. This enhanced phosphorylation of CD3ζ, ZAP70, and SLP-76 which augmented secretion of IFN-γ and TNF-α, by NK cells from healthy donors and AML patients. Thus, in addition to connecting immune cells to target cells, the clinical promise of engagers results from their ability to manipulate the nanoscale architecture of the immune synapse.